Great expectations: The construct validity of the violation‐of‐expectation method for studying infant cognition. Issue 6 (7th July 2022) - Stahl, Aimee E.; Kibbe, Melissa M.
Abstract: The violation‐of‐expectation method has been used in thousands of studies examining the breadth and depth of preverbal infants' knowledge and cognitive capacities. In this commentary, we review evidence that supports the violation‐of‐expectation method as an important tool for infant research that has strong construct validity. We show that this method reveals infants' expectations, produces reliable results across study designs and stimuli, and is grounded in theories of learning. We support and encourage the use of this method to continue to unveil the scope and sophistication of infant cognition.